Stabilization Methods in the Submerged Arc Discharge Synthesis of Carbon Nanostructures. (8th November 2021) - Hernandez-Tabares, Lorenzo; Darias-Gonzalez, Juan G.; Chao-Mujica, Frank J.; Ledo-Pereda, Luis M.; Antuch, Manuel; Carrillo-Barroso, Ernesto; Chong-Quero, J. Enrique; Reguera, Edilso; Desdin-Garcia, Luis F.
Abstract : Many papers, in which the submerged arc discharge (SAD) method in nanoparticle synthesis was used, reported similar operating parameters, but different electrode erosion rate values, different yields and purities of the obtained nanostructures, and a different sort of contaminants present in the synthesis. Analyzing these articles, we found insufficient attention to ensure the arc power stability, which is a key factor guaranteeing the product homogeneity and quality. This paper presents an analysis of different control strategies, remarks their advantages and drawbacks, and proposes the most appropriate technique to be used in SAD. The most appropriate technique is proposed from the SAD stabilization method analysis.